2019
DOI: 10.1097/pq9.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Initiation of Adequate Antimicrobial Therapy Using Real-Time Decision Support and Microarray Testing

Abstract: Introduction: Bloodstream infections (BSI) represent a common cause of sepsis and mortality in children. Early and adequate empirical antimicrobial therapy is a critical component of successful treatment of BSI. Rapid PCR-based diagnostic technologies, such as nucleic acid microarrays, can decrease the time needed to identify pathogens and antimicrobial resistance and have the potential to ensure patients are started on adequate antibiotics as early as possible. However, without appropriate proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…RAPID differs from previous CDSSs [ 11 , 12 ] by some of its designs: (1) complete coverage of all hospitalized adult patients, irrespective of services/departments; (2) inclusion of both bacteria and fungus in the database; and (3) working automatically, without the need of or increase in human workload. In addition, there are 2 unique characteristics that may account for the feasibility and effectiveness of RAPID:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RAPID differs from previous CDSSs [ 11 , 12 ] by some of its designs: (1) complete coverage of all hospitalized adult patients, irrespective of services/departments; (2) inclusion of both bacteria and fungus in the database; and (3) working automatically, without the need of or increase in human workload. In addition, there are 2 unique characteristics that may account for the feasibility and effectiveness of RAPID:…”
Section: Discussionmentioning
confidence: 99%
“…Another large study showed a similar result with an increased mortality rate of 0.3% among patients with community-onset bacteremia with each hour delay of antimicrobial treatment [ 9 ]. Several measures have been developed to reduce TAAT, including using a rapid species identification system [ 10 ], implementing multivariable models to assist empiric antibiotic selection [ 11 ], and setting up a clinical decision support pathway [ 12 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consider the following three example projects to (1) reduce in-room monitor-based alarms for patients and families, (2) improve antibiotic prescribing based on culture resistance profiles, and (3) drive proper handhygiene practice. [52][53][54] All three projects target key areas for improvement in patient experience, care delivery, and safety. Quality improvement teams may identify novel and compelling methods to deliver notifications considering their project aims and pay close attention to the burden of these notifications within the scope of their work.…”
Section: Beyond the Ehr: A Holistic View Of The Alert Ecosystemmentioning
confidence: 99%